(untitled) (The Research of Medical Science Review, 2025)
Background: The empirical evidence from clinical studies has demonstrated that massage as a form of touch therapy, can be effectively employed from infancy to promote the physical and neurological development of premature and underweight newborns. The purpose of current study is to evaluate the effectiveness of oil massage by comparing weight gain in low birth weight newborns using two different oils i.e. coconut oil and medium-chain triglyceride oil (MCT). Methodology: This randomized controlled trial was conducted at Children Hospital, Pakistan Institute of Medical Sciences (PIMS) after taking ethical approval from June to September of 2024. The study included a newborn that was older than 24 hours; Newborns that are hemodynamically stable, weigh less than 2500 grams at birth, and were born between 28 and 37 weeks gestational age, free of congenital or systemic illnesses. The study's exclusion criteria included the following: low birth weight newborns demonstrating sensitivity to coconut oil/MCT oil, receiving total parenteral nutrition (TPN) or intralipid therapy; and life-threatening abnormalities or anomalies. Additionally Parents whose consent was not to participate in the study were not included. Participants were randomly assigned to either the coconut oil or MCT oil massage group through lottery method. Weight was measured at enrolment and on day 15 of massage therapy in both the groups using a calibrated digital scale. Independent t-test was applied to compare mean birth weight among ‘coconut oil massage’ group and ‘MCT oil massage’ group. Result And Findings: The study revealed no statistically significant difference in the baseline weights between the MCT oil group (1432.80 ± 210.22 gm; p = 0.35) and the coconut oil group (1416.58 ± 267.98 gm). On Day 15, there was no significant difference in the final weights of the two groups, with the coconut oil group gaining weight at 1588.40 ± 273.67 gm and the MCT oil group gaining weight at 1533.30 ± 206.39 gm (p = 0.33). Conclusion: In conclusion, coconut oil is a cost-effective option and provides comparable weight gain to MCT oil, making it the preferred choice for neonatal care.